Comparison of ALIF vs. XLIF for L4/5 interbody fusion: pros, cons, and literature review - Winder, Mark J.; Gambhir, Shanu (Journal of Spine Surgery; Vol 2, No 1 (March 01, 2016): Journal of Spine Surgery, 2015)
The incidence of lumbar fusion for the treatment of various degenerative lumbar spine diseases has increased dramatically over the last twenty years. Many lumbar fusion techniques have been developed and popularized, each with its own advantages and disadvantages. Anterior lumbar interbody fusion (ALIF) initially introduced in the 1930’s, has become a common and widely accepted technique for lumbar fusions over the last decade offering several advantages over standard posterior lumbar interbody fusion (PLIF) or transforaminal lumbar interbody fusion (TLIF). More recently, the lateral trans-psoas approach termed extreme, direct or lateral lumbar interbody fusion (XLIF, DLIF, LLIF) is gaining widespread popularity. The aim of this paper is to compare the approaches, advantages and disadvantages of ALIF and XLIF for L4/5 interbody fusion based on relevant literature.